Peran Zikir Dalam Pembentukan Tawakal (Studi Atas Jamaâah Pengajian Malam Jumât Gus Lik Di Jamsaren Kota Kediri) - Umi Kulsum (Prodi Tasawuf dan Psikoterapi Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2018)
One of the most hard problems which is faced by modern societies now, especially Moeslim, is the hard life of competition. In this era, for those who can’t adapt the competition of life will experience a mental distress in dealing with it. To overcome that, The City of Kediri has a routine spiritual activity called by Pengajian Malam Jumat (PMJ) managed by Kyai Douglas Thoha Yahya (Gus Lik) which aims to guide and build people’s attitude with tawakal. Establishing tawakal (self-reliance to Allah) is an important study so that the community is educated in dealing with various problems of modernity. The purpose of this research was to determine the implementation of the PMJ zikir and the effect or respon for the jama’ah. This study uses qualitative method by case study approach with data collection by interview, observation and documentation. The results showed that the PMJ daâ€™wah content consisted of tawasuul, istighosah, zikir, pengajian, barzanji, mahkallul qiyam, mars Hubbul Waton and continued until closing prayer. The implementation of PMJ and zikir is routinely conducted at the Jamsaren mosque, Kediri, and would held on Wednesday night, Friday night and Saturday night. The five subjects explained that all of them feel peace and blesed because they can take part in the PMJ and a series of dzikr. In addition, the PMJ are able to make a person more muhasabah and more streghtened their faith. Then, the style da’wah by Gus Lik displays a full appreciation and is easily accepted by the all community